Non-adiabatic Quantum Dynamics of the Dissociative Charge Transfer He++H2 → He+H+H+ - De Fazio, Dario; Aguado, Alfredo; Petrongolo, Carlo (Frontiers in Chemistry, 2019)
We present the non-adiabatic, conical-intersection quantum dynamics of the title collision where reactants and products are in the ground electronic states. Initial-state-resolved reaction probabilities, total integral cross sections, and rate constants of two H2 vibrational states, v0 = 0 and 1, in the ground rotational state (j0 = 0) are obtained at collision energies Ecoll ≤ 3 eV. We employ the lowest two excited diabatic electronic states of HeH2+ and their electronic coupling, a coupled-channel time-dependent real wavepacket method, and a flux analysis. Both probabilities and cross sections present a few groups of resonances at low Ecoll, whose amplitudes decrease with the energy, due to an ion-induced dipole interaction in the entrance channel. At higher Ecoll, reaction probabilities and cross sections increase monotonically up to 3 eV, remaining however quite small. When H2 is in the v0 = 1 state, the reactivity increases by 2 orders of magnitude at the lowest energies and by 1 order at the highest ones. Initial-state resolved rate constants at room temperature are equal to 1.74 × 10−14 and to 1.98 × 10−12 cm3s−1 at v0 = 0 and 1, respectively. Test calculations for H2 at j0 = 1 show that the probabilities can be enhanced by a factor of 1/3, that is ortho-H2 seems 4 times more reactive than para-H2.